Adsorption of Fluoride from Aqueous Solution on Calcined and Uncalcined Layered Double Hydroxide - L.A. Ramírez-Llamas; R. Leyva-Ramos; A. Jacobo-Azuara; J.M. Martínez-Rosales; E.D. Isaacs-Paez (Adsorption Science & Technology)
The adsorption capacity of uncalcined and calcined layered double hydroxide (LDH) for fluoride removal was studied in this work. The LDH was synthesized by a co-precipitation method and calcined at various temperatures. The equilibrium data for fluoride adsorption on the LDHs were obtained in a batch adsorber, and the Freundlich isotherm model showed a better fit to the data. The LDH was chemically stable over the pH range of 5–12, but readily dissolved when the pH was below 5. The fluoride adsorption capacity of LDH decreased by raising the pH due to electrostatic interactions, and presented a maximum at 25 °C. The adsorption capacity of LDH was influenced by the calcination temperature and was enhanced by increasing the calcination temperature. The calcination destroyed the crystalline structure of the LDH, which was recovered when the calcined LDH was rehydrated in aqueous solution. The calcined LDH had a very high adsorption capacity towards fluoride.